Is dividend smoothing universal? - Chemmanur, Thomas J.; He, Jie; Hu, Gang; Liu, Helen (Journal of Corporate Finance, 2010)
In this paper, we develop new insights about the dynamics of corporate dividend policy by performing the natural experiment of comparing corporate dividend policies in Hong Kong and the U.S., two economies where the tax regime and equity ownership structure are significantly different. Our empirical results can be summarized as follows. First, a test of the Lintner model reveals that the extent of dividend smoothing by firms in Hong Kong is significantly less than those in the U.S. Second, the signaling effects of dividend changes on stock returns are stronger in the U.S. compared to those in Hong Kong. Third, our logit analysis of the determinants of dividend changes indicates that, while the lagged dividend yield significantly affects dividend changes in both countries in the same fashion, prior year stock returns have opposite effects on dividend changes in the two countries. Finally, the extent of dividend smoothing is not systematically related to blockholder equity ownership in either country. Overall, our results suggest that, compared to U.S. firms, Hong Kong firms pursue a more flexible dividend policy commensurate with earnings, and that the differences between the dividend policies of firms in the two countries are consistent with the signaling implications of the differences in the tax regime across the two countries.